Dysfunctional Family in Rainbow Rowell’s Fangirl - Dianisa Cintami Ananditha; Anik Cahyaning Rahayu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study is about Dysfunctional Family in Rainbow Rowell's Fangirl. This study applies the qualitative research design meanwhile the approach used is sociological approach. Two problems will be discussed in this study, namely signs of dysfunctional family and types of dysfunctional family. The data source is Fangirl by Rainbow Rowel. The novel is about Avery family who is characterized by a range of dysfunctional dynamics that impact each member of the family. From the analysis above, it can be concluded that analysis of this study consist two, which are the sign of dysfunctional family in Avery family potrayed by emotional abuse, neglect, blaming, hostility, conflict ,bad communication, and role reversal. The types of dysfunctional family in the Avery family can be characterized as having a chaotic family type, pathological family type, chronic conflict family type.